A comparison of alternative access routes for transcatheter aortic valve implantation. (3rd October 2018) - Overtchouk, Pavel; Modine, Thomas
ABSTRACT: Introduction : Alternative transcatheter aortic valve implantation (TAVI) approaches offer the possibility of valve replacement in patients ineligible to the transfemoral route. Authors provide an updated review of the existing alternative approaches. Areas covered : A systematic review of alternative approaches for TAVI was undertaken. The feasibility, safety, efficacy, and technical requirements of the transapical, transaortic, transcarotid, transsubclavian, and transcaval approaches have been compared. A multislice computed tomography is often necessary for pre-operative planning. Although the first developed, the transapical pathway tends to be abandoned because of its high morbidity. Transaortic approach requires a mini-sternotomy or thoracotomy and general anesthesia limiting its' acceptance. Transcarotid approach requires a mini-invasive surgical cutdown but is feasible under conscious sedation. Registry data provided reassurance regarding the stroke risk with the transcarotid approach. Transsubclavian pathway is recent and feasible percutaneously although necessitates additional complex maneuvers to avoid serious bleeding complications, which extends its' learning curve. Transcaval approach is still experimental but may benefit from technological advances. Expert commentary : The choice of the alternative approach dependents on patient anatomy and comorbidities, and local operator expertise and skills. Transaortic, transcarotid and transsubclavian are nowadays used the most. However, comparative data to favor one approach over another is lacking and further research is warranted.